(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Pseudohypoparathyroidism (PHP) is a rare hereditary disorder having the prevalence of 3.4 per million. It is characterized by symptoms and signs of hypoparathyroidism, typically in association with distinctive skeletal and developmental defects. The features of hypoparathyroidism are due to tissue resistance to the effect of parathyroid hormone (PTH). We will describe a 32-yearold woman who had recurrent convulsion for 16 years, infertility, cataract, psychosis, candidiasis and typical features of Albrights hereditary osteodystrophy (AHO), which include a round face, short neck, short stature and brachydactyly. Laboratory investigations showed hypocalcemia, hyperphosphatemia with high PTH level. Computed tomography scan of head revealed wide spread calcification in basal ganglia and cerebral hemispheres. X ray of left foot showed short left 4th metatarsal bone. The patient was diagnosed as a case of PHP on the basis of somatic features of AHO with typical biochemical abnormalities and uncontrolled convulsion with combined antiepileptic drugs for 16 years. The unusual features in our case are long delay in clinical diagnosis and absence of family history. She was treated with calcium salt and vitamin D. With this treatment patients condition was improved and she experiences no attack of convulsion and carpal spasm. Anticonvulsants were withdrawn gradually. We recommend that hypocalcaemia should be excluded before commencing anticonvulsant therapy in all epileptic patients and those patients whose seizures are refractory to anticonvulsant drugs DOI: http://dx.doi.org/10.3329/jbcps.v29i4.11331 J Bangladesh Coll Phys Surg 2011; 29: 227-230